Clinical and echocardiographic predictors of decompensation in acute severe aortic regurgitation due to infective endocarditis. Issue 4 (12th March 2021) - Chasapi, Athina; Mbonye, Kamatamu A.; Bajomo, Omotomilola; Young, William J.; Primus, Christopher; Ambekar, Shirish; Wong, Kit; Uppal, Rakesh; Davies, Lewis Ceri; Khanji, Mohammed Y.; Woldman, Simon; Lloyd, Guy; et al.
Abstract: Background: Patients with acute severe aortic regurgitation (AR) due to infective endocarditis can progress rapidly from the hemodynamically stable patient to pulmonary edema and cardiogenic shock. We sought to identify patients at risk of decompensation where emergent surgery should be undertaken. Methods: We identified 90 patients with acute severe AR from the echocardiography laboratory database. Baseline clinical, hemodynamic (heart rate (HR) and blood pressure (BP)), and echocardiographic data including mitral filling, premature mitral valve closure (PMVC), and diastolic mitral regurgitation (DMR) were identified. The primary endpoint was subsequent development of pulmonary edema or severe hemodynamic instability. Results: Patients who met the primary endpoint had a higher HR (98.5 bpm vs 80.5 bpm), lower diastolic BP (54 mm Hg vs 61.5 mm Hg), higher mitral E‐wave velocity (113 cm/s vs 83 cm/s), higher E / e ′ ratio (12.4 vs 8), higher proportion of DMR (27.8% vs 7.4%), and PMVC (25% vs 9.3%) than patients who did not meet the endpoint. The proportion of patients with the primary endpoint increased as HR increased ((≤81 bpm) 3/30 (10%), (81–94 bpm) 11/31 (35.5%), (≥94 bpm) 22/29 (75.9%), P < .0001) and as the diastolic BP reduced ((≤54 mm Hg) 19/31 (61.3%), (54–63 mm Hg) 12/31 (38.7%), (≥63 mm Hg) 5/28 (17.9%), P = .003). Independent predictors were a higher HR (OR 1.08 (95% CI 1.04–1.13) P = .0003) and DMR (OR 4.71 (95% CI 1.23–18.09), P = .02). Conclusion: Decompensation in acute severe AR is common. Independent predictors of decompensation are increasing HR(≥94 bpm) and the presence of DMR. Those with these adverse markers should be considered for emergent surgery.